Clinical and microbiological analysis of risk factors for breakthrough bloodstream infection during Tigecycline Therapy - Sol Jin; So Yun Lim; Yun Woo Lee; Heungsup Sung; Mi-Na Kim; Seongman Bae; Jiwon Jung; Min Jae Kim; Sung-Han Kim; Sang-Oh Lee; Sang-Ho Choi; Yang Soo Kim; et al. (Scientific Reports)
Abstract Background Tigecycline is widely used to treat a variety of bacterial infections despite concerns regarding increased mortality in severe infections. Previous case reports have documented breakthrough bloodstream infections (BSI) during tigecycline therapy. This study aimed to investigate the incidence of, and risk factors for, breakthrough BSI during tigecycline monotherapy. Methods A retrospective matched case–control study was conducted in a 2700-bed tertiary referral center, involving patients who received tigecycline monotherapy. Patients with breakthrough BSI (1:1) were matched with controls without breakthrough BSI based on age, sex, and date of tigecycline therapy. Results Of 4505 patients treated with tigecycline, 115 (2.6%, 95% confidence interval 2.1 to 3.1%) developed breakthrough BSI. The most frequently identified pathogen in breakthrough BSI was Klebsiella pneumoniae (22.8%), followed by Candida species (17.1%), Pseudomonas aeruginosa (16.3%), and Acinetobacter baumannii (14.6%). Of the K. pneumoniae and A. baumannii isolates for which tigecycline susceptibility results were available, 50% and 23%, respectively, were tigecycline-resistant (MIC > 2 mg/L). Intraabdominal (33.9%), catheter-related (30.4%), and hepatobiliary (19.1%) infections were the main sources of breakthrough BSI. In multivariable analysis, independent risk factors for breakthrough BSI during tigecycline therapy were liver cirrhosis (adjusted odds ratio [aOR], 3.09), indwelling catheter (aOR, 3.42), previous Candida colonization (aOR, 14.95), and previous multi-drug resistant bacteria colonization (aOR, 10.30). Conclusion In cases where there is a high suspicion of breakthrough BSI during tigecycline therapy, meticulous management and prudent selection of empirical antibiotics are crucial due to the diverse range of causative microorganisms involved.